The frequency of polycystic ovary syndrome in young reproductive females in Qatar - Sharif E; Rahman S; Zia Y; Rizk NM (Dove Medical Press, 2016)
Elham Sharif,1 Sumaya Rahman,1 Yumna Zia,1 Nasser M Rizk1,2 1Biomedical Sciences Department, College of Health Sciences, Qatar University, Doha, Qatar; 2Physiology Department, Mansoura Faculty of Medicine, Mansoura University, Mansoura, Egypt Abstract: This was a prospective cross-sectional study in which 126 female students between the ages of 18 and 30 years were evaluated for the frequency of polycystic ovary syndrome (PCOS) through clinical interview, questionnaire, and anthropometric measurements. The diagnostic criteria of the US National Institutes of Health criteria were used. Menstrual irregularities (MI) were identified, and clinical hyperandrogenism was evaluated by self-assessment of hirsutism using modified Ferriman–Gallwey score. Blood analysis was done for measurement of prolactin, thyroid-stimulating hormone, and the androgen hormones. Of all the students, 37 (30.8%) had MI, 38 (31.7%) had clinical hirsutism, 37 (30.8%) had acne, and 76 (63.3%) had a family history of type 2 diabetes. The estimated frequency of PCOS was 18.33% according to the US National Institutes of Health definition. Hormonal analysis demonstrated a significant increase in androgens (total testosterone, dehydroepiandrosterone sulfate, and free testosterone), and a significant decrease in sex hormone-binding globulin in our PCOS group, with a P-value <0.05. This study revealed a higher level of the androgen hormones among PCOS subjects with a frequency of PCOS (18.33%) similar to the global estimates of 10%–20%. Keywords: polycystic ovary syndrome, PCOS, hyperandrogenism, HA, hirsutism, menstrual irregularities, MI, frequency, hormonal profile, phenotype, Qatar, biochemical profile